“Barbed-Wire Boks” : the long shadow of the 1981 Springbok Tour of New Zealand and the United States of America - Potgieter, Sebastian Johann Shore (Stellenbosch : Stellenbosch University, 2017)
Thesis (MA)--Stellenbosch University, 2017.